Dealing with Soft Aperiodic Tasks in RUN - Nascimento, Flávia Maristela S.; Lima, George (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2023)
RUN is a scheduling policy designed for multiprocessor real-time systems, composed of periodic task sets with implicit deadlines, that guarantees up to 100% of processor utilization with reduced number of preemptions. In this paper we extend RUN to deal with task sets composed of both hard and soft tasks. Results are evaluated via simulation, which indicates that: RUN HS can deal with soft tasks; the average response time of aperiodic tasks is improved; hard deadlines are preserved while soft deadline miss ratio is kept low.